Enhancing student independence and creativity: Experimental research using PBL with flipped classroom - Arifin, Zainal (JURNAL PENDIDIKAN DAN PENGEMBANGAN MANUSIA, 2025)
Conventional learning still struggles to foster student independence and creativity, especially in the era of the Merdeka Curriculum, which emphasizes a flexible approach. The purpose of this study is to investigate how the flipped classroom-based project-based learning (PBL) model affects the independence and creativity of fifth-grade students at Pejagan 1 Elemntary School. Thru the use of a true experimental research design with a non-probability sampling method and IBM SPSS v.21 for data analysis, this approach was proven to significantly improve students' creativity (sig. 0.000 < 0.05) and students' independence (sig. 0.000 < 0.05). The results of this research are relevant to 21st-century learning and support the use of the Merdeka Curriculum. Teachers are advised to use this learning model to help students reach their full potential in a more autonomous and innovative way.